2018
DOI: 10.1111/acps.12957
|View full text |Cite
|
Sign up to set email alerts
|

New drug candidates for depression – a nationwide population‐based study

Abstract: The findings support the potential of agents acting on inflammation and the stress response system in depression as well as the potential of population-based registers to systematically identify drugs with repurposing potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
75
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 48 publications
12
75
1
2
Order By: Relevance
“…Epidemiological studies suggest that people taking aspirin or statins might be less likely to have concurrent depression [26][27][28][29][30], although the evidence is inconsistent, with some negative reports [31]. While there are positive randomised controlled trials of statins for the treatment of depression [32][33][34], and meta-analytic evidence for their effectiveness [35], no studies have investigated their therapeutic potential among youth.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies suggest that people taking aspirin or statins might be less likely to have concurrent depression [26][27][28][29][30], although the evidence is inconsistent, with some negative reports [31]. While there are positive randomised controlled trials of statins for the treatment of depression [32][33][34], and meta-analytic evidence for their effectiveness [35], no studies have investigated their therapeutic potential among youth.…”
Section: Introductionmentioning
confidence: 99%
“…As the majority of aspirin is used at low dose, the observed protective effect of aspirin on the studied disorders is likely driven by COX-1 inhibition. The null association of high-dose aspirin may on the other hand be due to additional inhibition of COX-2 [25]. In contrast, although non-aspirin NSAIDs have mixed selectivity, they are mostly selective for COX-2 inhibition or non-selective, possibly leading to the observed harmful effect of non-aspirin NSAIDs on these psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 26 relatively small randomized clinical trials suggested that NSAIDs play an antidepressant role in patients with major depressive disorder and are reasonably safe [ 24 ]. Preclinical studies indicate that the use of aspirin is associated with a lower risk of depression in the general population [ 25 ], and among patients with stroke [ 26 ] or osteoarthritis [ 27 ]. There is, however, a lack of evidence in this regard among cancer patients and on psychiatric disorders other than depression.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we also detected the expression of inflammatory response-related genes, including COX-2, IL-1β, PGE2, and MCP-1. Cyclooxygenase enzymes are critical for the synthesis of prostaglandins and participate in the inflammatory response process [24]. A previous study found that COX-2 directly affects the function of the CNS serotonergic system via the inflammatory process, and a higher level of serotonin in the frontal and temporoparietal cortices was observed after administration of rofecoxib, a selective inhibi-tor of COX-2 [37], restoring the basic function of the CNS system.…”
Section: Discussionmentioning
confidence: 99%